Stimulus‐Organism‐Response Reconsidered: An Evolutionary Step in Modeling (Consumer) Behavior - Jacoby, Jacob (Journal of Consumer Psychology, 2002)
The need to evolve the visual depictions of our consumer behavior models is addressed. Previous models are criticized for being constructions that fail to build on prior theory, and lack parsimony, comprehensiveness, coherence, and flexibility. More revolutionary movement in consumer behavior modelling is encouraged and an integrative Stimulus–Organism–Response framework is presented for consideration.